The impact of hot melt granulation method on propranolol hydrochloride physicochemical properties - Ilma Nugrahani; Hasan Rahmat; Joshita Djajadisastra (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2005)
Hot melt granulation is based on agglomeration by use of thermoplastic binder material that is solid at room temperature and softens and melts at higher temperature. By selecting a binder that is insoluble in water, melt granulation is a way of producing modified release granules, i.e. lipids/waxes to exhange the release of soluble drugs. The critical problem of this method is drugs instability because of heating. It has been studied the impact of hot melt granulation method on propranolol hydrochloride physicochemical properties. Physicochemical properties were evaluated including : water content titration – Karl Fischer, chemical structure analysis by Fourier Transforms Infrared Spectrophotometry (FTIR), and thermodynamic analysis by Differential Scanning Calorimetry (DSC). The results showed that hot melt granulation did not change the propranolol hydrochloride physicochemical structure but it changed anhydrate ß lactose to anhydrate a lactose. Key words : carnauba wax ; hot melt granulation; propranolol hydrochloride; physicochemical properties.